The Influence of Loneliness, Need to Belong, Social Presence, and Demographic Factors on Parasocial Relationships Among K-Pop Fans Using the Bubble App - Zahrotul Bahriyah; Latifa Rena (PROMOTOR, 2026)
This study used a quantitative approach with a total of 373 respondents who were K-pop fans using the Bubble app and who felt emotionally close to their idols. Sampling in this study used non-probability sampling with purposive sampling techniques. In determining the measurement tools, the researcher used tools that had been modified and adapted according to the needs of the study, including the Parasocial Interaction Scale (PSI) short version, De Jong Gierveld Loneliness Scale, Need to Belong Scale (NTBs), and The Social Presence Scale. To determine the validity of the measurement tools, the researchers used LISREL 8.8 software with CFA (Confirmatory Factor Analysis) techniques and tested the hypotheses using multiple regression techniques on the IBM SPSS 27 application. Based on the multiple regression test results, it was found that there was a significant influence of all independent variables on the dependent variable of 49.3%, while 50.7% was influenced by other variables outside this study. Based on the hypothesis test, four independent variables had a significant effect on the dependent variable, namely emotional loneliness, social loneliness, social presence, and frequency of bubble access. For further research, it is hoped that tests will be conducted on populations across Indonesia, fans who use other applications such as Weverse, Weibo, Instagram, or other applications, and research samples will be taken from various types of social media used by fans to support their activities.